2020
DOI: 10.18273/revsal.v52n4-2020007
|View full text |Cite
|
Sign up to set email alerts
|

Factores psicosociales del trabajo y efectos psicológicos en comerciantes informales en Morelos, México: Una exploración preliminar

Abstract: La mayor parte de la fuerza laboral en Latinoamérica está compuesta por personas que trabajan en la economía informal, a pesar de eso, son pocos los estudios que estudian los factores psicosociales laborales a los que se encuentran expuestas estas personas y sus consecuencias psicológicas, objetivo del presente estudio preliminar. Mediante una exploración cuanti-cualitativa se identificaron factores psicosociales, negativos y positivos, y su relación con la salud mental, el estrés, la satisfacción, el burnout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
2
0
4
Order By: Relevance
“…In addition to the influence of the aforementioned models, the PROPSIT was developed based on previous qualitative studies [23][24][25], which revealed the need for an exclusive instrument for use in the Latin American context, given the cultural differences and semantic limitations of other instruments created in industrialized countries [26]. Using a new qualitative-quantitative method in several iterations [23][24][25], work events that were perceived by workers as work stressors or sources of engagement were explored. These perceptions were categorized and structured into various dimensions and verified in other Mexican worker samples [26].…”
Section: The Psychosocial Work Processes Questionnaire (Propsit)mentioning
confidence: 99%
“…In addition to the influence of the aforementioned models, the PROPSIT was developed based on previous qualitative studies [23][24][25], which revealed the need for an exclusive instrument for use in the Latin American context, given the cultural differences and semantic limitations of other instruments created in industrialized countries [26]. Using a new qualitative-quantitative method in several iterations [23][24][25], work events that were perceived by workers as work stressors or sources of engagement were explored. These perceptions were categorized and structured into various dimensions and verified in other Mexican worker samples [26].…”
Section: The Psychosocial Work Processes Questionnaire (Propsit)mentioning
confidence: 99%
“…The validity study obtained high correlations with concurrent multiitem measures of job satisfaction, convergent measures of job support, divergent measures of stress and negativity, and associations with health [55]. In Mexico, its association with occupational stressors was theoretically consistent [57].…”
Section: Participantsmentioning
confidence: 86%
“…Cabe señalar que en población laboral informal mexicana destaca la tendencia notoriamente alta de aspectos positivos, como ha sucedido en otros estudios (Juárez-García et al 2020a). A su vez, el ítem 6 ("mi trabajo está lleno de retos"), que corresponde a dedicación, muestra una carga compleja que satura en el factor de absorción, lo que ha sido expuesto en estudios latinoamericanos (Flores-Jiménez et al 2015;Spontón et al 2012).…”
Section: Discussionunclassified
“…Por lo que refiere a las correlaciones interfactoriales, se observan valores altos (> 0.60) que discrepan de los resultados de otros estudios en población mexicana (Hernández Vargas et al 2016;Juárez et al 2015;Schafueli, 2011;Villavicencio-Ayub et al 2014), lo que puede deberse al uso de correlaciones policóricas como método robusto (Freiberg Hoffmann et al 2013) o a los factores psicosociales propios de los comerciantes informales mexicanos que son predominantemente más positivos, tales como las tareas gratificantes, la posibilidad de compartir con gente o la flexibilidad horaria (Juárez-García et al 2020a).…”
Section: Discussionunclassified
See 1 more Smart Citation